Potrzeby informacyjne przedsiębiorstw wchodzących na jednolity rynek europejski - Rudawska, Edyta (Companies' Entering European Market Information Needs, 2006)
Information is still more and more often perceived as an element which determines company's market equity. It enables risk reduction of decisions made by a company, cost reduction and improvements in effectiveness and as a result it increases company customers', employees' and shareholders' satisfaction. Having useful information seems especially important when broadening activities into new markets. The paper presents the selected results of marketing research dealing with companies' information reserves and the need and ways of gaining it by companies about EU market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 160-166